THE EXISTENCE OF THE EIGENVALUES FOR DIRAC’S TWO- PARAMETER BOUNDARY-VALUE PROBLEM - Harutunyan, T. N.; Sahakyan, G. H. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2006)
The existence of eigenvalues for Dirac’s two-parameter boundary-value problem is proved.